Research in fisheries science in selected Philippine universities an abstract bibliography, 1974-1995 - Gonzalez, Erlinda B.; Vallejo, Rosa M.; Maclean, John L. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study was undertaken to identify the research areas chosen by graduate students as the subject of their theses of dissertations in four selected universities namely; Central Luzon State University (CLSU), the University of the Philippines Diliman, Marine Science Institute and the Department of Meteorology and Oceanography (UP), the University of the Philippines in the Visayas (UPV), College of Fisheries, and the University of San Carlos (USC) in Cebu City for the following master's degrees: M.Sc. Aquaculture, M.Sc. Fisheries (Aquaculture), M.Sc. Fisheries (Fish Processing Technology), M.Sc. Fisheries Biology, M.Sc. Marine Biology and M.Sc. Oceanography. The period 1974-1995 was chosen, 1974 being the year when the first master's degree in fisheries was instituted at the University of the Philippines. A Total of 342 theses and 2 dissertations were identified and analyzed. It was also aimed at finding out if the research areas meet the national research priorities identified by their respective agencies, at the same time to produce an abstract bibliography of these theses and dissertations that will minimize or solve the problem of bibliographic control of unpublished theses and dissertations in fisheries-related subjects.
In the areas of study, the results show that 83 percent of the studies conducted were concentrated on three areas only namely; biology and ecology, nutrition and culture systems throughout the 21 year period, with biology and ecology as the most studied area. It also shows that 35 percent of the studies conducted for the master's degree in Aquaculture, Marine Biology and Marine Science and Fisheries Biology were concentrated on the biology and ecology study and 24 percent each on nutrition and culture systems. While fish health, taxonomy, genetics fishing gear, pollution and sociological aspects studies accounted for only 11 percent of the total studies. For the degree of M.Sc. in Fisheries (Fish Processing Technology), 16 or 5 percent of the studies were conducted considering that the degree have been implemented in 1981. Also, for the degree of M.Sc. in Oceanography which was implemented in 1974, a total of only 12 theses was produced before it was merged in 1991 with the master's degree, M.Sc. in Marine Biology to become M.Sc. in Marine Physical Science.
The study also shows that among the priority commodities for research identified by the Philippine Council for Agriculture and Resources Research and Development and the Bureau of Agricultural Research in 1983-1987 and 1988-1992 respectively, fishes are the most studied, followed by crustacea, algae and molluscs, etc. The commonly preferred species in aquaculture studies are tilapia, milkfish, and shrimp. Studies on tilapia are steadily increasing while studies on milkfish and shrimp were gradually declining over time. The most studied species in marine biology is algae both at UP and USC.
This study is in two parts, Part I consists of the introduction, review of related literature, methodology, presentation, analysis and interpretation of data, and the summary, conclusions and recommendations, including list of references and the appendices, Part II is the abstract bibliography consisting of 344 entries arranged by computerized Master File Number (MFN) and accompanied by the author, title, taxonomic and geographic indexes.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Fisheries -- Research -- Philippines; Fisheries -- Research -- Abstracts. -- Philippines; Fisheries -- Research -- Bibliography. -- Philippines